(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
Abstract: Transparency is a principle that guarantees access or freedom for everyone to obtain information about the administration of government, namely information about policies, the process of making and results achieved, transparency is needed and required to be done in institutions or any public institution that has an interest in the public, Building transparency in the management of zakat will create a good control system between two parties, namely institutions and stakeholders, because it does not only involve internal parties but also external parties. This research uses descriptive research type with a qualitative approach. Data collection techniques in this study used in-depth interview techniques with informants related to the research and also direct observation at the research location and using literature study. The purpose of this research is to be able to describe how the transparency of zakat fund distribution services at the office of the amil zakat agency in North Sulawesi province. Based on the results of the study it can be seen that the transparency of zakat services carried out by the amil zakat agency of North Sulawesi province has been done transparently, this can be seen from how the North Sulawesi provincial baznas, provide so much access to information, both through application services and directly , Baznas also often conducts the distribution process of zakat by inviting Muslims from various groups to get involved, although it can be seen that the involvement of the people in terms of supervision and involvement in the distribution process of zakat is still lacking, this can be seen from the lack of understanding of Muslims towards the management process zakat. Therefore, supervision and involvement of Muslims is needed for the management of zakat from the North Sulawesi provincial baznas keywords: transparency, management, service, zakat